Profile of Development of Critical Thinking Student Skills Assessment Instrument in the Course Geography of Disaster - Juita, Erna; Zulva, Rahmi; Edial, Helfia (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
In order to realize the goal of education, students are required to have critical thinking skills, especially in courses that are abstract like geography. Preliminary research has been done to find that the instruments used are not oriented to critical thinking skills. The purpose of this study is to know the process of developing critical thinking skills assessment instruments that meet the valid criteria. This type of research is development research by following the theory of device development according to Plomp (2013). The results show that the development of the device has been done only in the preliminary stage of research and prototyping phase. In the preliminary research stage the results obtained interviews with students and lecturers about the desired learning tool. At the phase prototyping phase obtained a good form of device to measure students' critical thinking skills.